The relation among steroid hormone levels, lipid profile and menopausal symptom severity - Cihan Kaya; Hüseyin Cengiz; Ali Yeşil; Murat Ekin; Levent Yaşar (Journal of Psychosomatic Obstetrics and Gynecology, 2017)
Introduction: Many postmenopausal women experience hot flashes, night sweats, non-specific emotional and psychological distresses. Our aim was to investigate the relation among steroid hormone levels, lipid profile and menopausal symptom severity using the menopause rating scale (MRS). Methods: A cross-sectional study was performed at our outpatient clinic with natural postmenopausal women. A total of 444 women were included in this study. The basic characteristics of the study population, such as age, gravidity, parity, time to menopause onset and body mass index (BMI) were recorded. Venous blood samples were collected from subjects after overnight fasting. The levels of high-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol, total cholesterol, triglyceride (TG), fasting plasma glucose, C-reactive protein, thyroid-stimulating hormone (TSH), cortisol, estradiol (E2), progesterone, testosterone and dehydroepiandrostenedione sulfate (DHEA-S) were analyzed. The MRS questionnaire validated for the Turkish population was used to assess the menopausal symptoms. Results: There was a statistically significant difference between mild and severe total symptom scores for TG, and elevated TG levels were observed in the severe group (p = 0.04). Elevated testosterone levels were observed with severe psychological symptom and total symptom scores. There were significant differences in progesterone level in psychological, urogenital, and total scores and lower levels were seen in severe symptom groups. There was a significant negative correlation between urogenital symptom scores and progesterone levels (p < 0.001). Discussion: Elevated levels of testosterone were related to severe psychological symptom and total menopausal symptom scores. A decrease in progesterone levels was related to high psychological, urogenital and total menopausal symptom scores. Elevated TG levels were also related to the total severe symptom scores.